Applications of Magnetite Nanoparticles in Cancer Immunotherapies: Present Hallmarks and Future Perspectives - Song, Qingle; Javid, Amaneh; Zhang, Guofang; Li, Yang (Frontiers in Immunology, 2021)
Current immuno-oncotherapeutic protocols that inhibit tumour immune evasion have demonstrated great clinical success. However, the therapeutic response is limited only to a percentage of patients, and the immune-related adverse events can compromise the therapeutic benefits. Therefore, improving cancer immunotherapeutic approaches that pursuing high tumour suppression efficiency and low side effects turn to be a clinical priority. Novel magnetite nanoparticles (MNPs) exhibit great potential for therapeutic and imaging applications by utilizing their properties of superparamagnetism, good biocompatibility, as well as the easy synthesis and modulation/functionalization. In particular, the MNPs can exert the magnetic hyperthermia to induce immunogenic cell death of tumour cells for effective antigen releasing and presentation, and meanwhile polarize tumour associated macrophages (TAMs) to M1 phenotype for improved tumour killing capability, thus enhancing the anti-tumour immune effects. Further, immune checkpoint antibodies, immune stimulating agents or tumour targeting agents can be decorated on MNPs, thereby improving their selectivity for the tumour or immune cells by the unique magnetic navigation capability of MNPs to promote the tumour killing immune therapeutics with fewer side effects. This mini-review summarizes the recent progress in MNPs-based immuno-oncotherapies, including activation of macrophage, promotion of cytotoxic T lymphocytes (CTLs) infiltration within tumours and modulation of immune checkpoint blockade, thus further supports the applications of MNPs in clinical therapeutic protocols.